Effect of Inorganic Vanadium Supplementation on Mineral Balance and Plasma Minerals in Karan Fries Calves - PAL, RAVI; Kumar, Rajesh; Mani, Veena; Kewalramani, Neelam; Datt, Chander; Singh, Digvijay (Indian Journal of Animal Nutrition, 2018)
To study the influence of vanadium (V) supplementation on mineral balance and plasma minerals, 24 male Karan fries calves of 3-6 month age and 72.85 kg mean body weight were selected and divided into four groups of 6 animals in each group. Calves in control group were fed a ration consisting of concentrate mixture, green fodder and wheat straw to meet their nutrient requirement (ICAR, 2013). Calves in treatment groups were additionally supplemented with 3, 6 and 9 ppm V in T1, T2 and T3 groups respectively. Experimental period was done for 165 days during which blood samples were collected at monthly intervals to study the effect of V supplementation on the plasma V, Ca, P, Mg, Fe, Zn and Cu concentration. Seven days metabolic trial was conducted at Â 7th fortnight of the experimental period to study the effect of V supplementation on retention of V, Ca, P, Mg, Fe, Zn and Cu. V supplementation improved the retention of vanadium, calcium, iron, copper and zinc (P<0.05) but had no effect on P and Mg in Karan fries calves. Plasma Ca, P, Mg, Fe, Zn and Cu level were similar among four groups but Plasma V level increased in supplemented groups. Hence, supplementation up to 9 ppm increased retention of Ca, Fe, Cu, Zn.